Political economy of fiscal deficits in a democracy - Eugene Okoi Ifere; Okoiarikpo Benjamin Okoi (EconomiA, 2018)
Studies on the impact of political considerations and gimmickry on the fiscal policy process in developing countries have largely been underappreciated and lacking. Therefore, this study set out to investigate how political actions impact fiscal deficits in Nigeria. The study employed descriptive and quantitative techniques using the Herfindahl index-based composition and turnover of the legislative and executive seats per party as well as that controlled by the ruling party. The results showed the prevalence of fiscal illusion among a significant proportion of voters; and that political considerations exert a significant impact on the implementation of fiscal deficits in Nigeria. Budgetary institutions were found to exert an insignificant impact on the fiscal policy process. Revitalization of the country's budgetary institutions and a reorientation and refocusing of media organizations to ensure objectivity in the reportage of government activities is recommended.
Keywords: 330; Political economy; Fiscal deficit; Turnover of legislative houses